Implementasi Ajaran Filsafat Keugaharian dan Konsep Lascarya dalam Pelaksanaan Yajna Agama Hindu - Trisnayani, Ni Nyoman (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The daily life philosophy in Hinduism teaches simplicity and self-control as the foundation of spiritual life. Meanwhile, concept lascarya emphasizes the implementation of yajna based on sincerity and not luxury. This research aims to analyze how these two concepts are implemented in the implementation of yajna by Hindus, especially in the modern context which tends to be consumerist and materialistic. The method used is literature study and analysis techniques in collecting data. The research results show that the implementation of daily life and lascarya in yajna can strengthen the spiritual value of the yajna itself, preventing people from showing off behavior (pratista), as well as encouraging more inclusive participation from all levels of society.